Tunable polarization components and electric field induced crystallization in polyvinylidenefluoride: A piezo polymer. Issue 1 (31st October 2018) - Ganguly, Ronit; Bandyopadhyay, Soumya; Miriyala, Kumaraswamy; Gunasekaran, Vijayabhaskar; Bhattacharya, Saswata; Acharyya, Amit; Ramadurai, Ranjith
Abstract: Polyvinylidenefluoride (PVDF) a semicrystalline pieozoelectric polymer was synthesized with varying process conditions and its ferroelectric domain orientations were studied using piezoresponse force microscope (PFM). PVDF thin films fabricated using tape casting technique with precursor solutions of varying viscosities reveal that the polarization components transform from a dominant planar to an out‐of‐plane configuration with increase in viscosity. Interestingly the planar components possessed a head to head or tail to tail kind of paired domains separated by a distance of ~ 380‐400 nm. Electrostatic energy minimization of an electrically inhomogeneous system containing similar domain arrangements as the experiments shows that the head to head and tail to tail arrangements with a minimum separation distance are more favorable than head to tail arrangements of domains. With increment of applied field, the domains grew in size and shape indicating amorphous to crystalline transformation of PVDF films. Such transformation was evident from X‐ray diffraction studies performed in‐situ in the presence of an applied electric field. Abstract : PVDF thin films possess tunable ferroelectric polarization components based on the synthesis conditions. A graphical configuration of the ferroelectric domains is shown in the image which possess a head to head or tail to tail configuration such that the electrostatic energy is minimum, with a vertical separation distance of 390 nm. Variation of X‐ray diffraction peak intensity of β‐phase of PVDF thin films in the presence of DC bias confirms the amorphous to crystalline transformation.